The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1073/pnas.1230540100
|View full text |Cite
|
Sign up to set email alerts
|

The transient receptor potential channel on the yeast vacuole is mechanosensitive

Abstract: Ca 2؉ is released from the vacuole into the yeast cytoplasm on an osmotic upshock, but how this upshock is perceived was unknown. We found the vacuolar channel, Yvc1p, to be mechanosensitive, showing that the Ca 2؉ conduit is also the sensing molecule. Although fragile, the yeast vacuole allows limited direct mechanical examination. Pressures at tens of millimeters of Hg (1 mmHg ‫؍‬ 133 Pa) activate the 400-pS Yvc1p conductance in whole-vacuole recording mode as well as in the excised cytoplasmic-side-out mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
125
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(127 citation statements)
references
References 49 publications
(62 reference statements)
2
125
0
Order By: Relevance
“…The recently identified yeast transient receptor potential channel homologue, Yvc1p, was shown to localize to the vacuolar membrane and mediate Ca 2ϩ efflux out of the vacuole (10). Additional reports have shown that vacuolar Ca 2ϩ efflux by Yvc1p can be specifically induced by hypotonic shock, which may be mediated by a mechano-sensitive mechanism (11,12).…”
mentioning
confidence: 99%
“…The recently identified yeast transient receptor potential channel homologue, Yvc1p, was shown to localize to the vacuolar membrane and mediate Ca 2ϩ efflux out of the vacuole (10). Additional reports have shown that vacuolar Ca 2ϩ efflux by Yvc1p can be specifically induced by hypotonic shock, which may be mediated by a mechano-sensitive mechanism (11,12).…”
mentioning
confidence: 99%
“…Corresponding to this role in vivo, TRPY1 was found to be mechanosensitive under patch clamp (13). Like its counterparts in animals, TRPY1 is polymodal and also can be activated by cytoplasmic Ca 2ϩ , likely amplifying its own activation through a Ca 2ϩ -induced Ca 2ϩ -release feedback (13).…”
mentioning
confidence: 99%
“…A TRP channel (TrpY1) is present in the vacuolar membrane of yeast and functions as a mechanosensitive channel (7,8). The finding that TrpY1 releases Ca 2ϩ upon hyperosmotic shock suggests that this intracellular mechanosensitive channel responds to environmental stress.…”
mentioning
confidence: 99%